Achillea vermicularis a medicinal plant from Iranian Traditional Medicine induces apoptosis in MCF-7 cells - M. Hamzeloo-Moghadam; A. Khalaj; M. Malekmohammadi; M. Mosaddegh (Iranian Society of Pharmacognosy, 2015)
Background and objectives: Achillea is an ancient medicinal herb. The genus comprises about 100 species which are mostly distributed in northern hemisphere and some have been investigated for different biological activities. There are also several reports in Iranian Traditional Medicine (ITM) texts about its anti-tumor effect. The cytotoxic activity of the methanol extract of Achillea vermicularis Trin.  has been reported in previous studies against different tumor cell lines. Based on these reports, the species has been further investigated for apoptosis induction ability. Methods: The apoptosis induction ability has been evaluated through activated caspase 3 investigation in intact MCF-7 cells in vitro.  Results: The assay demonstrated signs of caspase 3 activation in MCF-7 cells. Conclusion: Achillea vermicularis is suggested for further mechanistic evaluations in apoptosis studies.